Is the initial nest depth adapted to favorable conditions for the incipient colony in leaf-cutting ants? - Camargo, R. S. [UNESP]; Forti, L. C. [UNESP]; Matos, C. A.O. [UNESP]; Caldato, N. [UNESP]; Fonseca, O. S. [UNESP] (Universidade Estadual de Feira de Santana, 2016)
The nest dug by the leaf-cutter ant queen of the genus Atta is a vertical tunnel interconnected to a small chamber which holds its offspring and the symbiotic fungus. The depth of the initial chamber of the Atta sexdens rubropilosa ranges from 10 to 30 cm below the soil surface. With this information, we asked whether the ideal initial nest depth is adapted to favorable conditions for the initial colony. We hypothesized this depth can provide a minimum temperature range with almost constant temperature, leading to the development of symbiotic fungus and brood yet to emerge. To test this hypothesis, laboratory experiments were carried out and the soil temperature was measured at different depths. The colony development at different temperatures was studied in the laboratory and the brood production (number of eggs, larvae, pupae and adults) was measured until the first workers emergency. Additionally, lipid content and the survival of queens at different temperatures were determined. Our results show a suitable temperature range (ranging from 24.82±3.14°C to 24.11±1.30°C) at a depth of 5 to 25 cm from the ground, an ideal brood development at temperatures of 24 and 28 °C, and consequently a reduction in lipid content of the queens at high temperatures, without affecting their survival in the trial period. These results indicate that the depth of the initial chamber excavated by the queen is suitable for the success of the incipient colony.
Keywords: Atta sexdens; Claustral foundation; Leaf-cutting ants; Nest; Social insects